Cure Monitoring of Epoxy Structural Adhesion Using Lamb Waves and the Discrete Wavelet Transform - Zakharia, Michel (2024)
Epoxy adhesives have extensive applications in the aerospace industry. In this study, the curing behaviour of preimpregnated epoxy adhesive was monitored using guided ultrasonic Lamb waves. These waves were excited and recorded using ultrasonic transducers. This study aims to analyze the recorded Lamb wave data using the discrete wavelet transform (DWT). A 5-level DWT was performed on the recorded ultrasonic signals. The approximation and detail coefficients of the signals were analyzed to extract the evolution of the degree of cure (DOC) as a function of time. The results were then validated using differential scanning calorimetry (DSC). The results have shown that the DOC obtained from the DWT matches the one obtained using DSC. This method was able to detect the start time and end time of the curing process. The correlation between the two DOCs was found to be R2 = 0.68 indicating that ultrasonic Lamb waves can be used as a real time monitoring method for the degree of cure of a material during the manufacturing process.